THE PRESERVATION OF DAYAK SUANG ENSILAT LANGUAGE IN DUSUN NANGA ENTIBAB DESA NANGA DANGKAN KECAMATAN SILAT HULU KABUPATEN KAPUAS HULU - Elia Supranila; Yokie Prasetya Dharma; Herpanus Herpanus (Journal of English Educational Study (JEES), 2018)
The preservation of the Dayak Suang Ensilat language in the Dusun Nanga Entibab on the family environment is still maintained, besides it is also seen in the language use in the workplace environment, shop / market environment, youth environment, parents' environment, church environment, traditional ceremonies and environment the village used the Dayak Suang Ensilat language when communicating. The researcher found that there were three factors that influenced the Dayak Suang Ensilat language, which were still maintained, namely, the factors of loyalty, pride and population. Keywords: Preservation, Dayak Suang Ensilat.